The ordoliberal concept of "abuse" of a dominant position and its impact on Article 102 TFEU - Peter Behrens (Europa-Kolleg Hamburg, Institute for European Integration, 2015)
This paper explores the impact of ordoliberal thinking on the drafting of the prohibition of "abuse" of a dominant position in the market that was included in the competition rules of the Rome Treaty establishing the European Economic Community as well as on its interpretation by the Commission and the Court of Justice of the European Union (CJEU). Firstly, it is shown that the ordoliberal school must not be regarded as a set of ideas frozen in its formative period of 1933 to 1950 or 1957 when the "Freiburg School" was established but rather as an approach that has been dynamically developed and refined over the last 75 years (i.e. over four generations of ordoliberals) up to the present day by integrating important new insights without, however, giving up its core tenets and convictions. Secondly, it is shown on the basis of the preparatory work which lead in the 1950ies to the Rome Treaty that the adoption of the concept of "abuse" for the control of dominant undertakings was due to the strong influence of the German negotiating team that consisted of (in the meantime second generation) ordoliberals. Thirdly, it is explained how ordoliberal thinking about the "system of undistorted competition" and the protection of "residual competition against exclusionary practices" has influenced the application of the "abuse" concept in the jurisprudence of the Commission and the CJEU from the Continental Can case to the recent Intel case. This approach has come under attack from welfare-economic approaches which emphasize efficiency instead of competition and which have accused the ordoliberal approach of formalism, lack of sufficient economic analysis, preoccupation with fairness, protection of competitors instead of competition, obsession with interventionist regulation etc. This paper demonstrates that all of these characterizations are based on fundamental misunderstandings of what ordoliberal thinking originally meant and what it stands for today.
Keywords: 320; EU competition law; Rome Treaty; preparatory work; travaux préparatoires; monopoly problem; competition rules; abuse of a dominant position; ordoliberalism; Freiburg School; system of undistorted competition; protection of residual competition; exclusionary practices; predatory pricing; refusal to deal; essential facility; exploitation; efficiency; fairness; effects on competition